The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/ange.201103428
|View full text |Cite
|
Sign up to set email alerts
|

Activated Phenacenes from Phenylenes by Nickel‐Catalyzed Alkyne Cycloadditions

Abstract: Zickzackförmig, helical oder dazwischen: Angulare Phenylene addieren Alkine in [Ni(cod)(PMe3)2]‐katalysierten Prozessen bevorzugt in der Bucht‐Region. Die Umwandlungen ergeben neuartige spannungs‐ und elektronisch aktivierte Phenacene. Mechanistische Studien im Verbund mit DFT‐Rechnungen (R=Ph) liefern einen plausiblen Mechanismus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The twist angles θ 1 of the rings C and D were found to be 25.6 and 13.4°, respectively, whereas ring E is nearly planar—which is consistent with the results of the HOMA analysis that the rings C and D/E have weak and high aromaticity, respectively. The extent of distortion of the phenanthrene framework in compound 3 ( θ 2 =35.7°) is very close to those in 4,5‐dimethylphenanthrene (33.0°) and 5,6,7,8‐tetraphenyl[5]phenacene (31.1°) …”
Section: Resultsmentioning
confidence: 52%
“…The twist angles θ 1 of the rings C and D were found to be 25.6 and 13.4°, respectively, whereas ring E is nearly planar—which is consistent with the results of the HOMA analysis that the rings C and D/E have weak and high aromaticity, respectively. The extent of distortion of the phenanthrene framework in compound 3 ( θ 2 =35.7°) is very close to those in 4,5‐dimethylphenanthrene (33.0°) and 5,6,7,8‐tetraphenyl[5]phenacene (31.1°) …”
Section: Resultsmentioning
confidence: 52%
“…Although six four-membered rings are present in BC5, the MESP-based method suggests that the molecule may be stable and can be synthesized due to the dominance of aromatic character. In fact, the synthesis of BC5 is known in the literature, Vollhardt et al had reported the total synthesis of the first helical phenylenes (heliphenes), angular [6]-and [7]-phenylene, using a double cobalt-catalyzed cyclotrimerization strategy and a route for the preparation of such heliphene-based metal complexes. 6,68,69 The cyclic structure for three naphthalene−three cyclobutadiene-fused system NC32 is shown in Figure 8.…”
Section: ■ Methodologymentioning
confidence: 99%
“…Such a property provides useful hints for the design and synthesis of novel molecular frameworks . Many fused systems have been synthesized by connecting benzenoid hydrocarbons with antiaromatic cyclobutadiene, pentalene, indacene, and so forth. These systems have been successfully applied for the design of various organo-electronic devices. Cyclobutadiene, one of the classic antiaromatic organic molecules, has been used in the fused systems for modulating properties such as molecular conductivity, crystallization, segregation, thin-film formation, and so forth. The fused systems are also found to be appropriate for the development of semiconductor materials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to biphenylene itself, [ n ]phenylene has also been used as a substrate in transition metal‐catalyzed C–C bond activation. In 2011, Vollhardt and co‐workers reported Ni‐catalyzed [4+2] cycloaddition with alkyne to form phenacenes (Scheme ) . The C–C activation of angular [3]phenylene 36 proceeded with high regioselectivity for bay region, and both 38 and 39 were obtained.…”
Section: Reactions Of the Biphenylene Motifmentioning
confidence: 99%